2018
DOI: 10.1088/2040-8986/aad271
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in radiation-hardened fiber-based technologies for space applications

Abstract: In this topical review, the recent progress on radiation-hardened fiber-based technologies is detailed, focusing on examples for space applications. In the first part of the review, we introduce the operational principles of the various fiber-based technologies considered for use in radiation environments: passive optical fibers for data links, diagnostics, active optical fibers for amplifiers and laser sources as well as the different classes of point and distributed fiber sensors: gyroscopes, Bragg gratings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
111
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 199 publications
(114 citation statements)
references
References 260 publications
0
111
0
3
Order By: Relevance
“…In this case, there is an energy transfer between two ions in higher excited states which impairs both the pumping efficiency and population inversion and gives an extra heat load into the doped core since point defects inside the doped silica matrix occur. Usually this effect is negligible in active fibers in regular environment, but it becomes predominant when the fiber is exposed to radiation, going from few dB/km to few dB/m losses …”
Section: Thermal Effects On Eydfasmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, there is an energy transfer between two ions in higher excited states which impairs both the pumping efficiency and population inversion and gives an extra heat load into the doped core since point defects inside the doped silica matrix occur. Usually this effect is negligible in active fibers in regular environment, but it becomes predominant when the fiber is exposed to radiation, going from few dB/km to few dB/m losses …”
Section: Thermal Effects On Eydfasmentioning
confidence: 99%
“…For space applications in which Erbium‐Doped Fiber Amplifiers (EDFA) are used, it is clearly identified that the radiation‐affected component is the Erbium‐Doped Fiber (EDF) itself . For most of these fibers, such as those containing aluminum (Al) or phosphorous (P) in their silica‐based cores, the point defects causing the attenuation improvement of both pump and signal light are related to the dopants chosen for facilitating the active ion incorporation rather than to defects related to rare‐earth ions . Such amplifiers suffer of gain‐saturation problems when the output power grows up, so the co‐doping with ytterbium Yb 3+ sensitizer ions is an efficient way to overcome this drawback.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] gives a topical example). Then, the CC formation is due to ionizing radiations and it results into the so-called radiation-induced attenuation or RIA (see [4,5] for reviews of radiation effects). Space-based applications, where active fibers (in fiber optic gyroscopes or power laser sources) are simultaneously submitted to pumping and radiations, combine the PD and RIA issues and raise the question of their interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced defects have been extensively studied by the means of optical absorption (OA), luminescence, electron spin resonance (ESR) techniques and their combination (see [5,[13][14] for reviews). Almost all intrinsic and dopant-related CCs that have been identified so far in silica-based glasses have OA bands in the VIS and UV ranges (only one phosphorus-related color center, the P1 center, has a peak absorption at 1570 nm) [4,5,13]. For most of them, structural models have been debated, generation processes have been proposed in terms of photoionization or carrier trapping, and thermal stability has been assessed by isochronal annealing experiments [13][14][15].…”
Section: Introductionmentioning
confidence: 99%